The ESRI Energy Model - HYLAND, MARIE; DI COSMO, VALERIA (ESRI, 2012)
In Ireland, the energy sector has undergone significant change in the last forty years. In this period, there has been a significant increase in the demand for energy. This increase has been driven by economic and demographic factors. Although the current deep recession has quelled the upward trend in the demand for energy, a future economic recovery will bring these issues back into focus. This paper documents a model of the Irish energy sector which relates energy demand to real economic variables. As part of the HERMES macro?economic model this model of the energy sector has, for a number of years, been used to forecast energy demand. However, the energy model itself can be considered in isolation from the HERMES macro?economic model and this paper gives details of its specification.
PUBLISHED
Keywords: Energy Model; HERMES; macro?economic; energy demand model